2021
DOI: 10.3389/fchem.2021.667472
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Phospholipid Derivative Mediates Ion Transport Across Lipid Bilayers

Abstract: Inspired by the natural phospholipid structures for cell membrane, a synthetic phospholipid LC with an ion recognition group benzo-18-crown-6 (B18C6) moiety was prepared which has been demonstrated to be able to transport ions across the lipid bilayers. Fluorescent vesicle assay shows that LC has an excellent transport activity, and the EC50 value for K+ is 11.2 μM. The voltage clamp measurement exhibits regular square-like current signals with considerably long opening times, which indicates that LC achieves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The proton-pumping activity of the protein reconstituted into liposomes was measured by pyranine fluorescence. In another pyranine-based assay, a synthetic phospholipid LC ion channel for Rb + has been investigated using FCCP protonophore [138]. One issue with pyranine assays is the low dye entrapment efficiency in detergent-based reconstitution methods.…”
Section: Membrane-impermeable Dye-based Assaysmentioning
confidence: 99%
“…The proton-pumping activity of the protein reconstituted into liposomes was measured by pyranine fluorescence. In another pyranine-based assay, a synthetic phospholipid LC ion channel for Rb + has been investigated using FCCP protonophore [138]. One issue with pyranine assays is the low dye entrapment efficiency in detergent-based reconstitution methods.…”
Section: Membrane-impermeable Dye-based Assaysmentioning
confidence: 99%
“…4a ) motivated us to evaluate their ion transport activity across a lipid bilayer membrane. For a thermodynamically stable ion channel, the interactions between the ion and channel-forming molecules have to be sufficiently strong to compensate for the dehydration energy of the ion 60 . The supramolecular ion channel formed through an ion-induced self-assembled polymeric structure can be a good option for providing a static hydrophilic pathway for the ions to pass through the hydrophobic lipid bilayer membrane 61 64 .…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal ion transport in cell membranes can lead to a variety of diseases such as hypertension , and cystic fibrosis. , Therefore, accurate regulation of transmembrane ion flux is a necessary condition for maintaining normal life activities. Analyzing the functions of the naturally evolved ion transporters and designing higher active artificial versions have great potential applications in biomedicine. Unlike traditional membrane-spanning ion transporters, which mainly use channels or carriers to complete the passive transmembrane ion transport in cellular processes, in recent years, new ion transporters with unique transport mechanism have been explored. The type of artificial ion transporters inspired by molecular machines facilitate ion across membranes by shuttling, , swinging, swimming, fishing, and other mechanical motions, while exhibiting superior transport activity and remarkable ion selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Employing molecular dynamics (MD) simulations, Zhang et al found that the cooperation between shuttling and swinging movements of different components of [2]­rotaxane was the key to ion transport, and the latter was the rate-limiting step of that. In the past three years, scientists have developed a series of ion transporters based on the swinging motion with relay stations or seats to achieve efficient ion translocation. ,, Due to different transport mechanisms, these transporters differ significantly in ion transport activity and selectivity. Ye et al designed an artificial ion transport with a structure completely different from that of rotaxane, which has no fixed ion relay stations in the membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation